(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract— Rapid depletion of energy resources has immensely affected the cargo transportation industry. Efforts have been made to develop newer economic and environmental friendly modes for this purpose. Bulk solids can be transported for long distances effectively in pipelines. Raw materials can be stored in spherical containers (commonly known as capsules) transported through the pipeline. For economical and efficient design of any transportation mode, both the local flow characteristics and the global performance parameters need to be investigated. Published literature is severely limited in establishing the effects of local flow features on system characteristics of Hydraulic Capsule Pipelines (HCPs). The present study focuses on using a well-validated Computational Fluid Dynamics (CFD) based solver to simulate the unsteady turbulent flow of a spherical capsule as a simplified case in HCPs for onshore applications. A novel numerical model has been employed in the present study with the aid of the dynamic mesh technique for calculating the pressure and the velocity variations within such pipelines. The numerical model comprises a straight test section. The numerical model for capsule flow yields realistic results for the global flow parameters as compared to the experimental data from the test rig developed in the present study. The influence of the carrying fluid (water) on the capsule has been verified by estimating the shear forces and the friction coefficient. In addition, novel models have been developed for predicting the wet friction coefficient considering the start-up effect in such systems.